EPIDEMIOLOGICAL ASPECTS OF SOIL-TRANSMITTED HELMINTH INFECTION ON SCHOOL-AGE CHILDREN IN CIBODAS ELEMENTARY SCHOOL - Surya Pratama, Iman
Soil-transmitted helminth infection is one of neglected tropical disease while it has negative impact for individual and community health. In Indonesia, the prevalence of soil-transmitted helminth infection varying in range 2,2-96,3 %. School-age children are the most susceptible to soil-transmitted helminth infection. Epidemiology aspects i.e., prevalence, intensity, risk factor, and morbidity play an important roles in school-age children deworming program. Cross-sectional study was performed on 74 school-age children at Cibodas elementary school. Parasitology test on stool samples was done using McMaster method. Haemoglobin concentration in blood sample was determined using WHO Haemoglobin Colour Scale. Anthropometric measurements were taken to obtain stunting and wasting. Sosioeconomic, environmental and behavioural data were obtained by questionnaire and interview. Result showed the prevalence of single and mix soil-transmitted helminth infection were 18,92 and 22,60 %, respectively. Hookworm was the most common soil-transmitted helminth seen among the school. Intensity of the infection was relatively low based on egg per g category, i.e : 50-250 for roundworm, 100 for whipworm and 100-600 for hookworm. Bivariate analysis showed age, gender, father’s occupation, number of family members, presence of toilet, domestic animals, water sources, washing hands, wearing shoes, the consumption of raw vegetables and the use of anthelmintic drugs were not risk factors for soil-transmitted helminth infection at Cibodas elementary school. Based on heigh-for-age index and body mass index, the prevalence of malnutrition was 29,72% and 8,10%, respectively. Prevalence of anaemia at this school was 66,21%. Based on those results obtained, it can be concluded that intensity and prevalence of single soil-transmitted helminth infection at Cibodas elementary school was relatively low. Soil-transmitted helminth infection significantly associated with anaemia and malnutrition on school-age children at Cibodas elementary school.